(untitled) (Annals of Medical Research, 2025)
Aim: This study examined the impact of using a Nicardipine/Remifentanil combination inducing controlled hypotension (CH) in Functional Endoscopic Sinus Surgery (FESS). The goal was to minimize bleeding and enhance the visibility of the endoscopic field. The study focused on surgical field visibility, asccess, its hemodynamic consequences, and the impact on postoperative paraöeters such as nausea, vomiting, and pain. Materials and Methods: Our study included 73 patients whose age ranging between 18 and 65 years. The patients were randomly assigned to two groups. Group R (Remifentanil) (n=36) patients, and Group RN (Remifentanil/Nicardipine combination) (n=37) patients. Following intubation, In Group R, patients were administered an intravenous (IV) infusion of Remifentanil at a rate of 0.05–2.0 µg/kg/min, while Group RN received Remifentanil at 0.025–1 µg/kg/min, Nicardipine at 0.5–3.5 µg/kg/min. Target mean arterial pressure (MAP) was set at 50–65 mmHg. After the surgical procedure began, bleeding volume, suction requirements, and surgical field visibility were assessed at 15-minute intervals using the Boezaart scale. Duration of stay in the Post-Anesthesia Care Unit (PACU), incidence of nausea, vomiting, and pain assessment with the Numeric Rating Scale (NRS) were evaluated. Results: PACU length of stay was considerably shorter in Group RN compared to Group R (p=0.003). Pain scoring was greater in Group R (p=0.001). Nausea and vomiting scores were less in group RN (p=0.037). SAP and MAP were considerably lower in group RN (p=0.018 and p=0.023). HR values şin all time intervals were greater in group RN (p= ˂0.001). Boezaart score was lower in group RN during in all intervals (p= ˂0.001). Conclusion: The Remifentanil/Nicardipine combination provides better surgical field access and visibility byb inducing controlled hypotension (CH) in FESS. This combination is preferable over Remifentanil alone. It effectively maintains CH and shows greater success in reducing postoperative pain, nausea, and vomiting scores.